(untitled) (RT. A Journal on Research Policy and Evaluation, 2015)
University rankings represent a controversial issue in the debate about higher education policy. One of the best known university ranking is the Quacquarelli Symonds World University Rankings (QS), published annually since 2004 by Quacquarelli Symonds ltd, a company founded in 1990 and headquartered in London. QS provides a ranking based on a score calculated by weighting six different indicators. The 2015 edition, published in October 2015, introduced major methodological innovations and, as a consequence, many universities worldwide underwent major changes of their scores and ranks. Ben Sowter, head of division of intelligence unit of Quacquarelli Symonds, responds to 15 questions about the new QS methodology.